Faktor-Faktor Yang Mempengaruhi Keputusan Investasi Pada Perusahaan Infrastruktur, Utilitas Dan Transportasi - Priscilla W, Susanto Salim (Jurnal Paradigma Akuntansi, 2019)
The purpose of this study is to find out and analyze the influence of cash flow, liquidity, capital structure and debt policy on investment decisions. The research method used was purposive sampling with a total sample of 28 companies listed on the Indonesia Stock Exchange (IDX). This research was conducted using years of observation, namely 2014-2017. The type of data used is secondary data. Data is obtained from financial statements taken from www.idx.com. Data analysis method used is classical assumption analysis, descriptive statistical test, f test, t test and test coefficient of determination. Testing the hypothesis in this study uses the t test The results of the study show that the cash flow and leverage do not have a significant positive effect on investment decisions, while the liquidity and capital structure have a significant positive effect on investment decisions